Crystal structure of diisobutyl 2,5-dihydroxycyclohexa-1,4-diene-1,4-dicarboxylate, C16H24O6 - Li Zhuang-Yu; Liu E.; Liu Xiao-Jing; Jian Fang-Fang (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C16H24O6, triclinic, P1̄ (no. 2), a = 6.3410(13) Å, b = 7.3430(15) Å, c = 10.241(2) Å, α = 94.06(3)°, β = 103.89(3)°, γ = 113.13(3)°, V = 418.3(8) Å3, Z = 1, Rgt(F) = 0.0546, wRref(F2) = 0.1691, T = 295(3) K.